Une source ibāḍite à phrases berbères : le siyar de Bughṭūrī (écrit en 599/1202-3): II. – Étude externe (compléments) - Ould-Braham, Ouahmi (Études et Documents Berbères, 2024)
Keywords: Linguistique; Prosopographie -- Afrique du Nord

Pour une exploitation linguistique des anciens manuscrits berbères et arabo-berbères en graphie arabe. Essai de valorisation numérique - Meziani, Noumidya (Université El-Hadj Lakhdar, 2025)
Keywords: Linguistique

A lexicostatistical survey of northern Berber languages - Gravina, Richard (Brill's Journal of Afroasiatic Languages and Linguistics, 2024)
Abstract The Berber languages of North Africa comprise a collection of speech varieties where differences can be found as one moves across a Berber-speaking region, or from oasis to oasis. The varieties have a complex history, with multiple layers of contact, both with non-Berber languages and between Berber languages. These two factors make it difficult to categorise the relationships between Berber varieties, or to use the comparative method to provide a neat history of genetic developments. This paper uses lexicostatistical methods on a large dataset to provide a fine-grained picture of the synchronic relationships between Berber varieties, and thus to contribute to a broader understanding of the history and development of Berber.
Keywords: Linguistique

Un vocabulaire spécialisé du berbère médiéval à travers un glossaire bilingue publié par Bossoutrot (1900) - Ould-Braham, Ouahmi (Sur les traces de la langue amazighe (berbère) de l'Antiquité à nos jours, à l'appui de sources documentaires, 2024)
Keywords: Linguistique

A propos d'un nouveau manuscrit en tamazight du Moyen Âge - Brugnatelli, Vermondo (Sur les traces de la langue amazighe (berbère) de l'Antiquité à nos jours, à l'appui de sources documentaires, 2024)
Keywords: Linguistique

Constellations, plants and Arab poetry in a Medieval Berber text - Brugnatelli, Vermondo (Kervan. International Journal of African and Asian Studies, 2023)
This paper discusses one paragraph of the Kitāb al-Barbariyya, a medieval Berber commentary on Abū Ġānim’s Mudawwana. The brief note examined is a comment on the answer to a legal question, which mentions the ancient Berber names of a constellation and of a plant, quoting two lines of Arabic poetry. The passage occupies seven lines (f. 126b, ll. 8-14) of the manuscript MS.ARA 1936 found at the Bibliothèque universitaire des langues et civilisations (BULAC) of Paris. The Berber words retrieved from this text are Amanar, the name of the constellation of Orion, and tabduɣt, the name of the cotton plant. Moreover, in this ancient text, the word (a)kermus, which in the contemporary Berber languages applies to some specific plants (figs, prickly pears, dates), and which, in this case, seems to mean simply ‘fruit’, which supports a possible etymology from the Greek karpós. A list of Arab authors quoted within the Kitāb al-Barbariyya is added at the end of the paper.
Keywords: Fiqh -- Libye -- 8e siècle; Linguistique

Tamazight en Tunisie (2/2) Doucement, tranquillement… sûrement. - Ould Amar, Tahar (tasghunt taseklant, 2024)
Architecture adaptée à l’environnement et aux éventuelles agressions. …Nous Rentrons « chez nous » à Guellala, belle petite ville située au sud de l’Ile et  qui porte bien son  patronyme amazigh : aqellal  (la jarre). Entre deux ateliers de poterie s’insère un…autre atelier de poterie. Au centre de la coquète petite ville s’élève la jarre la plus haute […]
Keywords: Linguistique; Moeurs et coutumes -- Djerba; Récits de voyage -- Djerba

La langue Amazighe dans les écrits Ibadites - Messouaf, Youcef; Lamri, Wahid (مجلة اللغة الوظيفية, 2024)
La langue Amazighe était depuis des siècles une langue orale, elle vivait avec un statut inférieur par rapport aux autres langues écrites (Latine, Punique, Arabe), son utilisation était toujours par la voie de l’oralité. La formation des Etats en Afrique du Nord après l’apparition de l’islam était pour cette langue un nouveau souffle, et un moyen de redynamiser l’usage. Les Ibadites-Berbères faisaient recours à la langue Berbère pour diffuser le message religieux dans un milieu Berbère. La transcription de la langue Berbère durant cette période était un appui, puisque les savants religieux Ibadites utilisaient largement et quotidiennement ce moyen (les manuscrits en Berbère) pour faciliter la tâche aux prédicateurs qui voulaient infiltrer tous les espaces Berbères afin de généraliser cette nouvelle doctrine Ibadite.
Keywords: Linguistique

Berber isnin and “Defined Numerals” - Brugnatelli, Vermondo (The Handbook of Berber Linguistics, 2024)
This paper deals with “defined” numerals, i.e. numerals used in a context where the number of items is already known, like English ‘both’ (‘the two’). Quantifiers referring to two items like ‘both’ are quite widespread in the languages of the world, and most of the Berber languages, too, possess a word, isnin, which is evidently built on the numeral ‘two’ (sin) and means ‘both’. Nevertheless, some Berber languages also display numerals meaning ‘the three’, ‘the four’ etc. This paper aims at describing such peculiar numerals and at providing a diachronic explanation of their origin. This reconstruction implies the presence of the ancient morphemes of determination that nowadays have been merged into all nouns, losing their original meaning and becoming simple nominal marks.
Keywords: Linguistique

Pronominalization and clitic doubling in Syrian and Omani Arabic - Hallman, Peter; Balushi, Rashid al- (Linguistics, 2022)
Abstract This article treats cliticization of a pronoun to a syntactic host and doubling of the clitic pronoun with a non-pronominal counterpart in Syrian and Omani Arabic. Although the two varieties are closely related and the morphological paradigms they display are very similar, the pronominalization and clitic pronoun doubling patterns they display are quite different. We trace this difference to a basic difference in whether the relevant syntactic processes are sensitive to intervention effects in the two dialects, with the result being that the restrictiveness of pronominalization and clitic pronoun doubling patterns parallel the restrictiveness of basic word order patterns – whether double-object constructions are ‘symmetric’ or ‘asymmetric’ – with Syrian being the more restrictive of the two varieties.
Keywords: Linguistique

بين زوارة و زواوة هو نفس مابين آذار و ايّار (Facebook, 2024)
Keywords: Linguistique

اللغة الأمازيغية الابدال ‏النحو ‏الأمازيغي - يخلف, عيسى (‏المركز الليبي للدراسات الأمازيغية, 2022)
Keywords: Linguistique

La traduction de et vers Tamazight: Procédé ancien, essor récent. (Horizons, 2021)
La traduction a, de tout temps, permis l'acces a des cultures et savoirs venus d'ailleurs. Elle est une fenetre ouverte, au lecteur et au specialiste, sur des ouvrages qui ...
Keywords: Linguistique

Ibadi studies at the University of Milan-Bicocca - Brugnatelli, Vermondo (Giornata di studio su Storia e Cultura dell’Oman, 2021)
27 May 2021. Ibadi studies at the University of Milan-Bicocca Vermondo Brugnatelli (UMB) The Ibadi studies at the University of Milan-Bicocca started about 20 years ago, with a series of studies on the Berber language of the Ibadi community of Jerba, in Southern Tunisia. At the beginning, these researches were mostly devoted to linguistic issues, but they quickly switched to the wider field of literature and religious studies, after the discovery of a religious poem composed in the early 19th century by a Jerbian sheikh that belongs to a rich tradition among the Ibadi communities of Jerba, Mzab and Libya. Later on, the discovery of a huge manuscript in Medieval Berber containing a commentary on Abu Ghanim’s Mudawwana, opened another phase of the studies, namely the philological and codicological research on the Ibadi manuscripts, both in Berber and in Arabic. The existence of a small archive of documents retrieved in Libya by the Milanese scholar Eugenio Griffini at the beginning of the 19th Century is also exploited, and the publication of an unpublished Qasida from Jebel Nefusa (Libya) is currently under press. Over time, the researchers devoted to these studies in the Bicocca University have established a network of contacts with a number of colleagues around the world, in Oman as well as in the European and north African countries, some of whom have taken part in colloquiums in Milan, hosted by the Academia Ambrosiana. Vermondo Brugnatelli Vermondo Brugnatelli was born in Milan, where he also completed his studies in Hamito-Semitic (Afroasiatic) Linguistics. He is a specialist in historical linguistics and his main interests are particularly focused on the Berber world. He is currently Associate Professor at the University of Milano-Bicocca. He is director of the “Centro Studi Camito-Semitici di Milano” that he founded in 1993, president of the Berber Cultural Association in Italy and secretary of the Berber section of the class of African Studies in the “Academia Ambrosiana”. Besides editing and translating the largest collection of Berber folktales (in three volumes) published in Italian to date, he has carried out studies on many areas of Berber linguistics and literature . His field research is focused on the eastern Berber varieties, in particular those of southern Tunisia (Jerba and Cheninni). He is also carrying out researches on Ibadi texts in Berber from North Africa, both from oral and written sources. In particular, he has already published several articles on a medieval Berber commentary of Abu Ghanim
Keywords: Linguistique

Al-H̱alīl b. Aḥmad al-Farāhīdī, un genio dall’Oman - Faraj, Ali (Giornata di studio su Storia e Cultura dell’Oman, 2021)
Keywords: Linguistique

مُختاراتٌ لمخطوطاتٍ بالأمازيغيةِ الليبيَّةِ والتونسيَّةِ مِن حقبٍ مختلفة - وصف وتعليق - Brugnatelli, Vermondo (مجلة المناهل, 2020)
Keywords: Linguistique

تنفاس سق جربة: ‏حكايات أمازيغية جربية‏ - بن معمر, فتحي (ايباديكا - ‏دار منوال للنشر, 2020)
Keywords: Linguistique